Fasciola hepatica in Some Buffaloes and Cattle by PCR and Microscopy - Sultan Ayaz; Riaz Ullah; Naser M. AbdEl-Salam; Sumiara Shams; Sadaf Niaz (The Scientific World Journal)
Fasciolosis is the burning problem of the livestock rearing community having huge morbidity, mortality, and economic losses to livestock industries in our country Pakistan. The faecal and liver biopsy samplings were examined by polymerase chain reaction (PCR) and microscopy technique during the entire study. A total of 307 samples including 149 samples from Karak and 158 samples from Kohat abattoirs were examined by PCR method and overall prevalence of fasciolosis was 5.86% (18/307), amongst theses 8.05% (12/149) in liver biopsy and 3.79% (6/158) in feacal samples of cattle and Buffaloes were recorded. Similarly the microscopy based detection was 3.58% (11/307) including 4.61% (7/149) in liver biopsy and 2.5% (4/158) in faecal samples accordingly. Furthermore the areawise prevalence of fasciolosis in abattoirs by PCR method was found to be 7.59% (12/158) in Kohat and 4.02% (6/149) in Karak. A 618 pb DNA was amplified in 2% agarose gel electrophoreses. It is concluded from the study that prevalence of fasciolosis was higher in abattoir of district Kohat and PCR was a more sensitive method of diagnosis than microscopy.